Effects of phytosterols' intake on systemic and tissue-specific lipid metabolism in C57BL/6J mice - Zhu, Qian; Wu, Jingjing; Li, Jianling; Wang, Shengquan; He, Daxue; Lian, Xuemei (Frontiers in Nutrition, 2022)
To investigate the long-term effects of phytosterols intake on systemic and tissue specific lipid metabolism in C57BL/6J mice. Healthy male C57BL/6J mice were randomly divided into control diet group (CS) and phytosterols diet group (PS, 2% phytosterols). After 28 weeks of continuous feeding, serums, livers and lungs were collected for targeted free sterols quantification, biochemical tests, lipid profile detection and RNA-seq analysis. Compared with the CS group, 2% phytosterols supplementation significantly increased campesterol concentrations and its ratio to cholesterol in the serum, liver and lung of mice, with cholestanol concentrations and its ratio to cholesterol decreased. Total cholesterol (TC) levels were reduced in the serum of the PS group (P<0.05), with the triglyceride (TG) levels unchanged. In response to the decreased circulating cholesterol concentration, the expression of endogenous cholesterol synthesis genes was up-regulated in the liver, but caused no obvious lipid accumulation and inflammatory cell infiltration. While, for peripheral tissues, long-term phytosterols-fed mice exhibited diminished cholesterol synthesis, fatty acid transport and oxidation in the lung. The results provided clear indication that 2% phytosterols diet effectively reduced circulating total cholesterol levels in the healthy mice, with tissue specific lipid metabolic regulation in the liver and lung.